Bioassay-guided isolation of antiplasmodial compounds from two Malaysian Kopsia species / Nor Hadiani Ismail, Khalijah Awang and Faridahanim Mohd Jaafar - Ismail, Nor Hadiani; Awang, Khalijah; Mohd Jaafar, Faridahanim (Research Management Institute (RMI), 2010)
In our search for antiplasmodial compounds from Malaysian plants, two plants from genus Kopsia (family Annonaceae) that are Kopsia terengganensis and Kopsia teoi were investigated. Based on the traditional use of this plant for treating fever, we had carried out the study on the antiplasmodial effect of Kopsia terengganensis. This study was undertaken to investigate the possibility of antimalarial activity of K terengganensis and K teoi. by isolating of the phytochemicals from the extracts and active fractions of K terengganensis and K teoi, identifying the structures of the purified phytochemicals using spectroscopic methods and determining the antiplasmodial activity. Chromatographic separation and isolation procedures on K terenganensis yielded the alkaloids larutensine (1), eburnamine (2), akuammidine (3), eburnaminol (4), rhazidigenine (5), quebrachamine (6), isoeburnamine (7) and eburnamonine (8). From Kopsia teoi, rhazimol (9), kopsinginol (10), kopsigine (11), ebumamenine (12), akuammiline (13), isoeburnamine (7) and kopsinol (14) were obtained. Compounds coded 5011-14 CRYS, 3P2, RJ-18 and 5035 H₂0 showed strong inhibition with IC50 values below 5 μg/mL. The strongest inhibition was shown by compound 5011-14 CRYS with IC₅₀ 0.11 μg/mL. Compounds RAW1 and 5035 H CRYS showed moderate inhibition with IC₅₀ values of 10.09 and 16.72 μg/ml, respectively. Further work on these compounds is being pursued based on the promising activities shown. This data suggests that K terengganensis and K. teoi are potential source of antimalarial agents.